Time-Series Forecasting of Ethereum Price using Long Short-Term Memory (LSTM) Networks - Al-Wasee, Mohammad Samin; Kundu, Promee Shankar; Mahzabeen, Israt; Tamim, Tasnim (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.